Anatomy of the skull of a leopard cat (Felis bengalensis) - SARMA, K; NASHIRUDDULLAH, N; ISLAM, S (The Indian Journal of Animal Sciences, 2014)
Gross anatomical study was conducted on the sklill of an adult leopard cat. The skull could be divided into 4 surfaces, viz. frontal, lateral, nuchal and basal surfaces. The frontal bone was much convex as compared to the parietal and nasal bones. The temporal fossa was shallow and the facial crest was absent. The orbits were directed more rostrally towards the median plane. The paracondylar processes were very sharp. The tympanic bulla was large and oriented caudolaterally, on the other hand, peuous temporal bone was very small. The minor palatine foramina were found to be absem.